Implementation of the An-Nahdliyah Method in an Effort to Improve the Quality of Learning to Read the Qur'an at RTQ Darul Falah - Azizah, Ani Nur; As’ari, Hasyim; Hayati, Rina Mida (International Journal on Advanced Science, Education, and Religion, 2025)
This study aims to describe the learning journey at RTQ Darul Falah in Seputih Banyak, Central Lampung, which implements the an-Nahdliyah method in its educational approach. Despite being an established religious educational institution, RTQ Darul Falah continues to face challenges, particularly in students' ability to read and write the Qur’an. To address this issue, the institution adopts the an-Nahdliyah method as a strategy to enhance students' learning quality in Qur’anic literacy. This research employs a qualitative approach, with data collected through observations, interviews, and documentation. The findings reveal that the an-Nahdliyah method significantly contributes to improving students’ ability to read the Qur’an, supporting the overall effectiveness of learning in TPQ or RTQ environments. This research contributes to the field of Islamic education by highlighting the effectiveness of the an-Nahdliyah method in enhancing Qur’anic literacy among students. It provides a practical reference for religious educational institutions facing similar challenges, offering insight into effective teaching strategies rooted in traditional methodologies